Adaptation of a dietary survey for use in a longitudinal study from the sociocultural context of a population of German colonization - Da Rosa, Ana Carolina; Schmitz, Bruna; Chiarelli, Graciella; da Silveira, João Luiz Gurgel Calvet; Alves, Maria Urania; Campanella, Luciane Coutinho de Azevedo (Journal of Health Care, 2016)
Introduction. The assessment tools in dietary habits need to be validated considering the specificities of the culturally determined eating habits of the population groups. Objective. To present a methodology to adapt an instrument for assessing the pattern of food intake - the food frequency questionnaire (FFQ) - for population of the municipality of Pomerode, SC, Brazil. Methodology. A qualitative approach using focus groups as a technique. From the exploration, coding and data analysis of the material collected, 21 foods were added and 17 were excluded from the starting FFQ, resulting in 33.33% of changes. Considerations. The use of focus groups proved to be an appropriate technique for the adaptation of the food frequency questionnaire, resulting in food inclusions and exclusions identified by the participants themselves in their sociocultural context, qualifying the preceding step for validation and reproducibility, so that from their results, correct and useful dietary information for subsequent inferences can be obtained.